From feed to flow: watching television on TikTok - Siles González, Ignacio (2025)
This paper investigates how users engage with content on TikTok that was originally produced for television. Based on interviews with participants in Costa Rica, we argue that watching television content on TikTok provides valuable insights into the future trajectories of both television and new media. To this end, we first demonstrate that TikTok's television flow (in Raymond Williams' sense) is "co-programed" through user interaction with algorithms, rather than being universally predetermined. We then posit the notion of "uncommitted attention" to argue that watching television on TikTok involves active engagement with content and texto-material conditions that make this experience fleeting and unstable. Finally, we examine how users establish cross-platform flows between TikTok and their broader media environments. In this way, we offer insights into how ontologically ambivalent platforms such as TikTok reconfigure traditional television watching.